Capital Account Convertibility : A New Model for Developing Countries - Quirk, Peter (IMF Working Papers; Working Paper, 1994)
This paper analyzes issues for developing countries considering a move to capital account convertibility. It reviews the relevant literature, including arguments for sequencing, and analyses in a series of charts various features of the foreign exchange market impact of removing controls, as against the alternative of foreign exchange intervention. Finally, it examines recent experiences of capital account liberalization by developing countries in the context of multi-pronged stabilization programs.